2015
DOI: 10.1080/14786419.2015.1013470
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive glycosides from the African medicinal plantBoerhavia erectaL.

Abstract: Phytochemical studies of the previously unexplored stem of Boerhavia erecta from Burkina Faso, resulted in the isolation of an unreported glycoside 4, 2,3-dihydroxypropylbenzoate-3-O-β-[4″-methoxy] glucuronide as well as seven known glycosides (1-3, 5-8). The major isolate 5 and 8 indicated a significant inhibition against HIV integrase (IC50 10 and 22 μg/mL, respectively). The extracts and isolates were also tested for antimalarial activity, but insignificant activity was observed. Disciplines AbstractPhyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Analysis of the 1 H-NMR spectrum of C. lunata isolate RJ01 EPS showed the presence of proton signals in the region of 2.5 to 4.2 ppm (Figure 3). The proton signal showed a chemical shift of the sugar proton signals (Nugraha et al 2015). Chen et al (2016) and Ge et al (2013) also observed several EPS proton signals on the spectrum of water-soluble polysaccharides from Alternaria sp.…”
Section: Nuclear Magnetic Resonance Spectroscopy Of Epsmentioning
confidence: 81%
“…Analysis of the 1 H-NMR spectrum of C. lunata isolate RJ01 EPS showed the presence of proton signals in the region of 2.5 to 4.2 ppm (Figure 3). The proton signal showed a chemical shift of the sugar proton signals (Nugraha et al 2015). Chen et al (2016) and Ge et al (2013) also observed several EPS proton signals on the spectrum of water-soluble polysaccharides from Alternaria sp.…”
Section: Nuclear Magnetic Resonance Spectroscopy Of Epsmentioning
confidence: 81%
“…Repeated column chromatography of the ZYCH extract resulted in the isolation of 25 known compounds (Compounds 1 - 25 , Supplementary Figure 1 ). The compounds were identified as chinensin ( 1 ) (Lopez et al, 1996 ), (–)-matairesinol ( 2 ) (Umezawa et al, 1991 ), octacosanoic acid ( 3 ) (Chen et al, 2013 ), diphyllin ( 4 ) (Annapoorani et al, 1984 ), kaerophyllin ( 5 ) (Mikaya et al, 1981 ), α-peltatin ( 6 ) (Raffauf et al, 1987 ), butyrolactone ( 7 ) (Li et al, 2006 ), demethylyatein ( 8 ) (Sanfeliciano et al, 1991 ), bupleurumin ( 9 ) (Kim and Yun-Choi, 2007 ), suchilactone ( 10 ) (Banerji et al, 1984 ), matairesinol monoglucoside ( 11 ) (Sakamura et al, 1980 ), indigoticalignanoside A ( 12 ) (Zhang et al, 2013 ), (–)-matairesinol 4-O-glucoside ( 13 ) (Yang et al, 2015 ), vanillic acid 4-β-D-glucoside ( 14 ) (Nugraha et al, 2015 ), wenchuanensin ( 15 ) (Luo et al, 1993 ), kaempferol 3-O-neohesperidoside ( 16 ) (Budzianowski et al, 1985 ), asicariside b1 ( 17 ) (Sasaki et al, 2013 ), citroside A( 18 ) (Cho et al, 2014 ), dehydrodiconiferyl alcohol 4-O-β-D-glucopyranoside ( 19 ) (Tan et al, 2005 ), saikosaponin B 2 ( 20 ) (Ishii et al, 1980 ), styraxlignolide C ( 21 ) (Di et al, 2013 ), 11α-methoxy saikosaponin F ( 22 ) (Ding et al, 1986 ), saikosaponin H ( 23 ) (Shimizu et al, 1985 ), clinoposaponin XI ( 24 ) (Mori et al, 1994 ), saikosaponin C ( 25 ) (Ishii et al, 1980 ). The above compounds were isolated from this plant for the first time except compounds 1 , 3 , 20 , and 25 .…”
Section: Resultsmentioning
confidence: 99%